Russian literary-critical reception of Burns at turning of the XIX–XX centuries - Zhatkin, Dmitry (Opción, 2019)
The article is devoted to the specifics of the Russian literary-critical reception of Burns at the turn of the XIX–XX centuries that is methodologically based on the works of the classics Russian literary criticism, as well as on the works, concerning the problems of the Russian-English literary. It has resulted that literary and artistic understanding of the creative work of Burns is connected with the activities of leading Russian scientists and the emergence of translation studies. As a conclusion, it is necessary to recognize Robert Burns as one of such writers, who is, unfortunately, too little popular with us.